De nuevo sobre los judíos granadinos al tiempo de su expulsión - Ladero Quesada, Miguel-Ángel (En la España Medieval, 2007)
Records of the embarkation at Almuñécar in June 1492 of 1485 Jews from Granada expelled by the Catholic Monarchs. Their insertion in 268 “houses” and geographical origins, the goods they carried, anthroponyms and other related facts. The second part of the article details over 400 debts that the Jews left unpaid and the crown subsequently recovered, with information on the location, amount, Muslim and Jewish anthroponyms, economic activities, prices, merchandise and currency.